Spatiotemporal Pattern Evolution of Urban Ecosystem Resilience Based on “Resistance-Adaptation-Vitality”: A Case Study of Nanchang City - Duo, Linghua; Li, Yanan; Zhang, Ming; Zhao, Yuxi; Wu, Zhenhua; Zhao, Dongxue (Frontiers in Earth Science, 2022)
With the rapid development of the economy and society in recent years, the ecological environment has deteriorated significantly, and governments at all levels, departments and relevant scholars have begun to pay attention to urban ecological construction and research on urban disaster prevention and mitigation, and the concept of resilience has gained widespread attention in this context. This study explores the complex dynamic evolution mechanism of urban ecosystem resilience based on the three characteristics of resilience, and selects Nanchang, an important ecological barrier in the middle and lower reaches of the Yangtze River and a model area for integrated management of the Great Lakes Basin, as an assessment target. This study establishes a quantitative measurement and evaluation framework for urban ecological resilience in three dimensions: resistance, adaptation and vitality, and conducts a comprehensive evaluation of urban ecosystem resilience. The results show that the trend of land-use change from 1990 to 2020 is mainly characterized by the continuous decrease of arable land and ecological land (forest land, grassland, water) and the continuous increase of construction land, among which, the land use dynamic attitude of construction land is the largest, reaching 5.33% from 1990 to 2005. During the study period, the overall ecosystem resilience of Nanchang showed a gradual decline and was always at a moderate to low level, with a long-term distribution pattern of "low in the middle and high in the surroundings" and a clear spatial heterogeneity. This study helps to clarify the regional ecosystem security status and provides a reference for exploring the complex dynamic evolution mechanism of ecological resilience.